"Keep it secret, keep it safe": Information poverty, information norms, and stigma. Issue 5 (11th March 2013) - Lingel, Jessa; boyd, danah
<x xml:space="preserve">Abstract</x> When information practices are understood to be shaped by social context, privilege and marginalization alternately affect not only access to, but also use of information resources. In the context of information, privilege, and community, politics of marginalization drive stigmatized groups to develop collective norms for locating, sharing, and hiding information. In this paper, we investigate the information practices of a subcultural community whose activities are both stigmatized and of uncertain legal status: the extreme body modification community. We use the construct of information poverty to analyze the experiences of 18 people who had obtained, were interested in obtaining, or had performed extreme body modification procedures. With a holistic understanding of how members of this community use information, we complicate information poverty by working through concepts of stigma and community norms. Our research contributes to human information behavior scholarship on marginalized groups and to Internet studies research on how communities negotiate collective norms of information sharing online.